Tightrope Walking: Balancing Leadership Roles and Partnerships with Undergraduate Student Assistants in SoTL Research - Bjartveit, Carolyn; Kandola, Simran (Imagining SoTL, 2025)
In this reflective essay, a researcher relates her experience of supporting partnerships with undergraduate student research assistants (RAs) during a SoTL study. Unexpected changes to the ethics requirements after the study had received approval and commenced resulted in changing the leadership roles of the research team members and adjusting procedures for facilitating interviews with the study participants. Although unsettling at the time, these modifications opened valuable opportunities for the RAs to co-facilitate focus group interviews and hone their leadership and research skills. Reflections on the researcher’s and a student RA’s experiences exemplify the SoTL principles of “respect, reciprocity, and shared responsibility” in supporting student partnerships (Cook-Sather et al., 2014, p. 27). Expanding further by recognizing rights as a principle promotes equal faculty-student research partnerships and acknowledges the knowledge, professional experience, and leadership skills that undergraduate student RAs contribute to SoTL studies and project work.